2017
DOI: 10.1515/commun-2017-0003
|View full text |Cite
|
Sign up to set email alerts
|

“Your profile is so rad”: Self-presentation strategies in Turkish adolescents

Abstract: Social networking sites like Facebook are popular and ever-expanding, especially among adolescents in Turkey. The study of 406 adolescents aged 14 to 18 (Mage = 15.61, SD = 1.16) provides novel insights into how adolescents from Turkey within a specific cultural framework, display certain kinds of self-presentation strategies. Using the Revised Self-Presentation Scale (RSPS; Lee et al., 1999) when coding adolescents’ profiles for strategies and information, we found that exemplification is the most utilize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…On the other hand, the Internet is a "global village" of individuals from various nationalities and cultural backgrounds with nearly 60% of the online population residing outside of the U.S. [44]. These diverse offline cultural values can be reflected in the online [45]- [52]. Additionally, there may be values and goals specific to the SNS context outside of the values that users bring with them [53].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the Internet is a "global village" of individuals from various nationalities and cultural backgrounds with nearly 60% of the online population residing outside of the U.S. [44]. These diverse offline cultural values can be reflected in the online [45]- [52]. Additionally, there may be values and goals specific to the SNS context outside of the values that users bring with them [53].…”
Section: Discussionmentioning
confidence: 99%
“…Their result revealed that self-presentation predicted altruistic behaviour of adolescents in China. Boz & Guan [71] carried out an investigation on self-presentation strategies among adolescents in Turkey and found exemplification and ingratiation as strong predictors of self-presentation among adults. Adawiyah [28] investigated the effects of impression management tactics on individual performance in Indonesia.…”
Section: -3-impression Management and Employee Contextual Performancementioning
confidence: 99%